Saúde bucal na atenção primária à saúde com ênfase no câncer de boca: uma revisão integrativa de literatura entre os anos de 2011 e 2022 - PORTELA, Camila Maria da Silva (Universidade Federal do Oeste do Pará, 2024)
Introduction: Primary Health Care (PHC) is one of the pillars of health and the gateway to the Unified Health System (SUS), being an oral health team responsible for continuous care in the PHC, control and prevention of diseases such as oral cancer of multifactorial etiology, and is among the main causes of death from neoplasms, since most cases are those with disease progression. Objective: Conduct an integrative literature review on oral health in the primary health care network, emphasizing oral cancer between the years 2011 and 2022. Methodology: This is an Integrative Literature Review, using the following descriptors: Oral Health, Oral Cancer, Primary Health Care. Performed at the Virtual Health Library (VHL) using the following inclusion criteria: full texts, in Portuguese, published between 2011 and 2022; and Scientific Electronic Library Online (Scielo) and as inclusion criteria: articles, the language in Portuguese, between the years 2011 and 2022. Results: The work selected 20 articles published and indexed in different databases, in VHL using the DeCS (Oral Health) AND (Mouth Cancer) AND (Primary Health Care), and in Scielo with the same descriptors, filters, exclusions. The data showed that all professionals working in the Family Health Strategy are ideal for cancer screening, however the dentist is primarily responsible for carrying out the diagnosis of lesions, there is a notorious lack of fusion between the performance of prevention and diagnosis actions. of mouth cancer. There are many obstacles in relation to the therapeutic itinerary that the user goes through in the service, which influences a worse prognosis of the disease. If necessary, conducting a better approach to oral cancer from graduation to training and improvement of these professionals. Final Considerations: The study listed the main works that relate oral health in PHC to individuals with oral cancer, in which it was possible to identify risk factors such as smoking, alcoholism, viral infections by the human papillomavirus, gender, age, genetics, nutritional status, environment, lifestyle and habits, socioeconomic factors and prolonged exposure to solar radiation. In addition to presenting the dental surgeon as the key player in the diagnosis of lesions. Therefore, the importance of PHC in oral cancer is based on the addition of oral health professionals in the ESF for first-contact access to the population with preventive measures for early detection and immediate treatment.